Manajemen multidisiplin Oral Squamous Cell Carcinoma (OSCC): laporan kasus - Ni Putu Riskayanti; Dahlia Riyanto; Saka Winias (DiscoverSys Inc., 2021)
Background: Oral squamous cell carcinoma (OSCC) is the most common type of oral cancer and represents more than 90% of all head and neck cancers. The etiology of OSCC is multifactorial. The uses of tobacco, heavy alcohol drinking, less consumption of vegetables and fruit, genetics, trauma and viruses are considered possible risk factors of the OSCC. This case study aims to evaluate the multidiscipline management of OSCC at Universitas Airlangga Dental and Oral Hospital, Surabaya, Indonesia.Case Presentation: This case report presents a 45-year-old female patient who came with chief complaints of ulcer on the lateral right of the tongue that persistent for 3 months ago. The patient also complained of pain when speaking, eating, swallowing, and the pain felt into the right head. The patient has no history of tobacco and alcohol consumption, but her sister has a history of breast cancer. No extraoral abnormalities were found. Intraoral examination results showed a single ulcer with induration on the lateral dextra of the tongue and diffuse pseudomembranous on the dorsal of the tongue. Based on history taking and clinical examination, the patient was suspected of OSCC. The management included debridement of the lesion, complete blood count, fasting blood glucose, HbA1c, and anatomical pathology examination. The patient has also been prescribed anesthetics, antiinflammation and antiseptic mouthwash. The patient was then referred to the head and neck oncologist for hemiglossectomy. Two months after the surgery, there is no complaint of the lateral right of the tongue. The patient also has no complaint about eating and swallowing.Conclusion: The dentist plays an important role in identifying OSCC. The early diagnosis and proper multidisciplinary management of OSCC could improve the prognosis of the case and the patient's life quality. Latar belakang: Oral squamous cell carcinoma (OSCC) adalah jenis kanker mulut yang paling umum dan ditemukan hampir pada 90% dari semua kasus karsinoma di rongga mulut. Etiologi OSCC adalah multifaktorial. Penggunaan tembakau, konsumsi alkohol berlebihan, konsumsi sayur dan buah yang lebih sedikit, genetika, trauma dan virus dianggap sebagai faktor risiko OSCC. Laporan kasus ini bertujuan untuk mengevaluasi manajemen multidisipin OSCC pada Rumah Sakit Gigi dan Mulut (RSGM) Universitas Airlangga, Surabaya, Indonesia.Presentasi Kasus: laporan kasus ini menyajikan kasus seorang pasien wanita berusia 45 tahun yang datang dengan keluhan utama ulserasi pada lateral lidah kanan yang menetap sejak 3 bulan yang lalu. Pasien juga mengeluh nyeri saat berbicara, makan, menelan dan nyeri terasa di kepala kanan. Pasien tidak memiliki riwayat konsumsi tembakau dan alkohol tetapi saudara perempuannya memiliki riwayat kanker payudara. Tidak ditemukan kelainan ekstraoral. Hasil pemeriksaan intraoral menunjukkan ulser tunggal dengan indurasi pada lateral lidah dekstra dan pseudomembran difus pada dorsal lidah. Berdasarkan anamnesis dan pemeriksaan klinis, diagnosa sementara adalah OSCC. Penatalaksanaan meliputi debridement lesi, hitung darah lengkap, glukosa darah puasa, HbA1c, dan pemeriksaan patologi anatomi. Pasien juga diresepkan obat kumur anestetikum, antiinflamasi dan antiseptik. Pasien kemudian dirujuk ke Departemen Bedah Onkologi Kepala Leher untuk dilakukan hemiglosektomi. Dua bulan setelah operasi, tidak ada keluhan pada lidah pasien. Pasien juga tidak memiliki keluhan saat makan dan menelan.Simpulan: Dokter gigi memiliki peran yang penting dalam mengidentifikasi OSCC. Diagnosis dini dan manajemen multidisplin tepat dapat meningkatkan prognosis kasus dan kualitas hidup pasien.